Pengaruh Media Wordwall Terhadap Peningkatan Penguasaan Kosakata Bahasa Inggris Kelas V SDN KETEJER - Wawan Mulyadi; Muh. Bisyrulhafi; Siti Niami (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
Vocabulary mastery is one of the important aspects of learning English because it is the basis for the development of listening, speaking, reading, and writing skills. However, the results of initial observations in grade V of SDN Ketejer show that students' mastery of English vocabulary is still low due to learning dominated by conventional methods. This study aims to analyze the influence of the use of Wordwall media on the mastery of English vocabulary of grade V students of SDN Ketejer. This study uses a quantitative approach with a pre-experimental method and a One-Group Pretest–Posttest design. The research sample amounted to 32 students who were selected using the total sampling technique. The research instrument is in the form of multiple-choice tests that have met the validity and reliability tests. Data analysis was conducted using descriptive statistics, the Shapiro–Wilk normality test, the paired t-test, and the Normalized Gain (N-Gain) test with IBM SPSS Statistics 25. The results showed that the average student score increased from 43.56 in the pretest to 80.44 in the posttest. The results of the Paired Sample t-Test obtained a significance value of 0.000 (p < 0.05), which shows that the use of Wordwall media has a significant effect on students' English vocabulary mastery. In addition, the N-Gain test result of 0.6483 (64.83%) was included in the medium category, which shows that the use of Wordwall provides an effective increase in vocabulary mastery. The findings of this study show that Wordwall media can serve as an alternative digital learning medium to increase student engagement and support more active, interactive, and meaningful learning of English vocabulary through the application of the Four Strands Framework.